Pengaruh Profitabilitas, Kepemilikan Institusional, dan Ukuran Perusahaan terhadap Pengungkapan Keberlanjutan Indeks LQ45 - Arhamni, Muhammad Insan; Noor, Ice Nasyrah (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
This study aims to analyze the influence of three key factors—profitability, institutional ownership, and company size—on the level of sustainability disclosure. The research focuses on prominent companies listed on the LQ45 Index of the Indonesia Stock Exchange. In measuring the variables, profitability is assessed using Return on Assets (ROA), reflecting the company's efficiency. Institutional ownership is analyzed based on the proportion of shares held by domestic institutions. Meanwhile, company size is evaluated through the total assets recorded at the end of the current year period. Research data was collected from company annual reports and sustainability reports for the 2022-2024 period. The analysis results indicate that profitability and institutional ownership do not have a significant influence on sustainability disclosure. However, company size was found to have a positive and significant influence. This finding suggests that larger companies tend to exhibit broader transparency in their sustainability reporting in the Indonesian capital market.